Search for neutral Higgs bosons in e(+)e(-) collisions at root s=183 GeV - Abreu, P; Adam, W; Adye, T; Adzic, A; Ajinenko, I; Albrecht, Z; Alderweireld, T; Alekseev, G; Alemany, R; Allmendinger, T; Allport, P; Almehed, S; et al. (1999)
Neutral Higgs bosons were searched for in the data collected by DELPHI at a centre-of-mass energy of 183 GeV, corresponding to an integrated luminosity of 54 pb-1. The production of the lightest neutral Higgs boson with either an on-shell Z boson or a neutral pseudo-scalar Higgs boson was analysed. Lower limits at the 95% confidence level were obtained on the Higgs boson masses. The limits are 85.7 GeV/c2 for the Standard Model Higgs boson and 74.4 GeV/c2 for the scalar and 75.3 GeV/c2 for the pseudo-scalar Higgs bosons as predicted by the minimal super-symmetric extension of the Standard Model with commonly used assumptions on the model parameters, plus the assumption that the mass of the pseudo-scalar boson is greater than 20 GeV/c2. These results significantly improve the limits reached with previous data.